Lipid raft‐disrupting miltefosine preferentially induces the death of colorectal cancer stem‐like cells - So‐Yeon Park (Wiley, 2021)
Abstract Background Lipid rafts (LRs), cholesterol‐enriched microdomains on cell membranes, are increasingly viewed as signalling platforms governing critical facets of cancer progression. The phenotype of cancer stem‐like cells (CSCs) presents significant hurdles for successful cancer treatment, and the expression of several CSC markers is associated with LR integrity. However, LR implications in CSCs remain unclear. Methods This study evaluated the biological and molecular functions of LRs in colorectal cancer (CRC) by using an LR‐disrupting alkylphospholipid (APL) drug, miltefosine. The mechanistic role of miltefosine in CSC inhibition was examined through normal or tumour intestinal mouse organoid, human CRC cell, CRC xenograft and miltefosine treatment gene expression profile analyses. Results Miltefosine suppresses CSC populations and their self‐renewal activities in CRC cells, a CSC‐targeting effect leading to irreversible disruption of tumour‐initiating potential in vivo. Mechanistically, miltefosine reduced the expression of a set of genes, leading to stem cell death. Among them, miltefosine transcriptionally inhibited checkpoint kinase 1 (CHEK1), indicating that LR integrity is essential for CHEK1 expression regulation. In isolated CD44high CSCs, we found that CSCs exhibited stronger therapy resistance than non‐CSC counterparts by preventing cell death through CHEK1‐mediated cell cycle checkpoints. However, inhibition of the LR/CHEK1 axis by miltefosine released cell cycle checkpoints, forcing CSCs to enter inappropriate mitosis with accumulated DNA damage and resulting in catastrophic cell death. Conclusion Our findings underscore the therapeutic potential of LR‐targeting APLs for CRC treatment that overcomes the therapy‐resistant phenotype of CSCs, highlighting the importance of the LR/CHEK1 axis as a novel mechanism of APLs.